Sophie Calle & Paul Auster: Doubles-jeux (Palíndromo, 2019)
An introduction to Doubles-jeux, a set of 7 artists’ books by Sophie Cal-le, done in collaboration with American novelist Paul Auster. This text was written in European Portuguese.
Keywords: artists’ books; performance; autobiography; fiction